Association analysis between the C516T polymorphism in the 5-HT2A receptor gene and schizophrenia Análise de associação entre o polimorfismo C516T do gene do receptor 5-HT2A e esquizofrenia - Vivian Bertola; Quirino Cordeiro; Stevin Zung; Elisabete Cristina Miracca; Homero Vallada (Arquivos de Neuro-Psiquiatria)
Data from epidemiological studies have demonstrated that genetics is an important risk factor for schizophrenia. Disturbances of serotonergic brain pathways have been implicated in the pathophysiology of schizophrenia. Some studies have suggested that the efficacy of atypical antipsychotics on schizophrenia treatment may be related to the serotonin 2A receptor (5-HT2A), and that serotonergic drugs may induce psychotic symptoms. Thus, the aim of this study was to investigate the association between the C516T polymorphism and schizophrenia in a Brazilian population composed by 246 patients and 315 healthy matched controls in a case-control approach. No statistically differences were observed in allelic (chi2=1.77, 1d.f., p=0.18) or genotypic (chi2=1.69, 2d.f., p=0.42) distributions between cases and controls. The results suggest that the C516T polymorphism of the 5-HT2A receptor gene is not related to the susceptibility for schizophrenia in our Brazilian sample. Estudos epidemiológicos têm demonstrado que o componente genético é importante fator de risco para o desenvolvimento de esquizofrenia. Alterações nas vias cerebrais serotonérgicas têm sido relacionadas à fisiopatologia da esquizofrenia. Algumas investigações têm sugerido que a eficácia de antipsicóticos atípicos no tratamento da esquizofrenia pode estar relacionada com sua ação no receptor de serotonina subtipo 2A (5-HT2A), e que drogas serotonérgicas podem provocar sintomas psicóticos. Assim, o objetivo desta investigação foi examinar a associação entre o polimorfismo C516T do gene do receptor 5-HT2A e esquizofrenia em uma amostra brasileira composta por 246 pacientes e 315 controles saudáveis e pareados em um estudo tipo caso-controle. Não foram observadas diferenças na distribuição alélica (chi2=1,77, 1d.f., p=0,18, 1d.f.) e genotípica (chi2=1,69, 2d.f., p=0,42) entre os grupos de pacientes e controles. Os resultados sugerem que o polimorfismo C516T gene do receptor 5-HT2A não é fator de susceptibilidade para esquizofrenia na amostra brasileira estudada.